2016
DOI: 10.1002/ijch.201600098
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Alkoxide‐Directed Metallacycle‐Mediated Annulative Cross‐Coupling Chemistry

Abstract: Alkoxide-directed metallacycle-mediated cross-coupling is a rapidly growing area of reaction methodology in organic chemistry. Over the last decade, developments have resulted in > thirty new and highly selective intermolecular (or “convergent”) C–C bond-forming reactions that have established powerful retrosynthetic relationships in stereoselective synthesis. While early studies were focused on developing transformations that forge a single C–C bond by way of a functionalized and unsaturated metallacyclopenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Thus, the b-stabilization from the alkyne substituent does not play a dominant role in determining relative selectivity, and other factors such as the relative strength of the forming Ti-C Si bond vs. Ti-C M bond may also be involved: for example, Micalizio has demonstrated that insertion into 2-silyl-3-stannyltitanacyclopropenes will occur on the Ti-C Sn bond compared to the Ti-C Si bond. 45,46…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the b-stabilization from the alkyne substituent does not play a dominant role in determining relative selectivity, and other factors such as the relative strength of the forming Ti-C Si bond vs. Ti-C M bond may also be involved: for example, Micalizio has demonstrated that insertion into 2-silyl-3-stannyltitanacyclopropenes will occur on the Ti-C Sn bond compared to the Ti-C Si bond. 45,46…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the b-stabilization from the alkyne substituent does not play a dominant role in determining relative selectivity, and other factors such as the relative strength of the forming Ti-CSi bond vs Ti-CM bond may also be involved: for example, Micalizio has demonstrated that insertion into 2-silyl-3-stannyltitanacyclopropenes will occur on the Ti-CSn bond compared to the Ti-CSi bond. 35,36 Figure 5. Directing group strength comparisons.…”
Section: Resultsmentioning
confidence: 99%
“…Pendent alkoxide directing groups have been used extensively in Ti-catalyzed and mediated reactions to engender regio-, chemo-, and enantioselective transformations . For example, Sharpless’ catalytic asymmetric alkene epoxidation relies on alkoxide directing groups to engender enantiofacial selectivity, while more recently Micalizio has used alkoxides to direct alkyne insertion regioselectivity in Ti-mediated reductive coupling reactions (Figure , middle), ,, and Burns has used alkoxides to direct stereoselective alkene dihalogenation and haloazidation reactions. Alkoxide-directed coupling reactions have also served as a platform for heterocycle syntheses, such as pyridines and indolizidines. , …”
Section: Introductionmentioning
confidence: 99%